PENURUNAN STUNTING MELALUI PEMBERIAN MAKANANTAMBAHAN: STRATEGI PENCEGAHAN DAN PERAWATANNUTRISI BALITA DI DESA WAY NGISON KECAMATAN BATUKETULIS KABUPATEN LAMPUNG BARAT - Gatot Bintoro Putra Aji (Yayasan Baitul Hikmah al-Zain, 2026)
Stunting is a condition of growth failure in childrenunder five caused by chronic malnutrition, resulting in childrenhaving a height that is not appropriate for their age. Thiscommunity service activity aimed to increase public awarenessregarding stunting prevention through the provision ofsupplementary feeding programs and Vitamin A in Way NgisonVillage. This study used a descriptive approach with qualitativeand quantitative methods. Data were collected through interviewsand documentation, then analyzed descriptively to drawconclusions. The results showed that the reduction in stuntingcases in Way Ngison Village reached 50%; however, the outcomewas not yet optimal because the reduction target throughsupplementary feeding and Vitamin A programs should havereached 80%. This condition was influenced by the lack ofawareness and support from parents regarding stuntingprevention efforts. Through this program, students conductedsocialization activities on the importance of early stuntingprevention through supplementary feeding and Vitamin Aadministration for toddlers. Due to the limited duration of thecommunity service program, data regarding changes in stuntingprevalence after Vitamin A administration were not yet available.